Telocytes are associated with tissue remodeling and angiogenesis during the postlactational involution of the mammary gland in gerbils - Sanches, Bruno D. A. (2020)
The postlactational involution of the mammary gland is a complex process. It involves the collapse of the alveoli and the remodeling of the extracellular matrix, which in turn implies a complex set of interrelations between the epithelial, stromal, and extracellular matrix elements. The telocytes, a new type of CD34-positive stromal cell that differs from fibroblasts in morphological terms and gene expression, were detected in the stroma of several tissues, including the mammary gland; however, their function remains elusive. The present study employed three-dimensional reconstructions and immunohistochemical, ultrastructural, and immunofluorescence techniques in histological sections of the mammary gland of the Mongolian gerbil during lactation and postlactational involution to evaluate the presence of telocytes and to investigate a possible function for these cells. By means of immunofluorescence assays for CD34 and c-kit, major markers of telocytes, and also through morphological and ultrastructural evidences, telocytes were observed to surround the mammary ducts and collapsing alveoli. It was also found that these cells are associated with matrix metalloproteinase 9, which indicates that telocytes can play a role in extracellular matrix digestion, as well as vascular endothelial growth factor, a factor that promotes angiogenesis. Together, these data indicate that telocytes are a distinct cell type in the mammary gland and, for the first time, show that these cells possibly play a role in tissue remodeling and angiogenesis during the postlactional involution of the mammary gland.